2012
DOI: 10.1111/j.1445-2197.2011.05998.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of trastuzumab in Australia and New Zealand: results from the National Breast Cancer Audit

Abstract: Trastuzumab-prescribing trends conform to the published guidelines. However, older patients and those with HER-2 positive, node-negative tumours >1 cm may be undertreated in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Additionally, estimates of trastuzumab use at the time of data collection or reporting might not be reflective of current treatment patterns or guidelines. It should also be noted that several studies in patients with EBC reported findings on the basis of data from patients who were diagnosed and/or treated between 2005 and 2008 (Table 1), 23,25,30,31,36,40,41,44 which might not have captured or been sufficient to fully characterize trastuzumab use after expanded approvals for adjuvant or neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, estimates of trastuzumab use at the time of data collection or reporting might not be reflective of current treatment patterns or guidelines. It should also be noted that several studies in patients with EBC reported findings on the basis of data from patients who were diagnosed and/or treated between 2005 and 2008 (Table 1), 23,25,30,31,36,40,41,44 which might not have captured or been sufficient to fully characterize trastuzumab use after expanded approvals for adjuvant or neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Observational studies on real-world treatment patterns in patients diagnosed with and/or treated for HER2 þ EBC between 2005 and 2015 suggest that 19.1% to 59.5% in the United States, Canada, Australia, New Zealand, United Kingdom, The Netherlands, Germany, and China did not receive neoadjuvant or adjuvant trastuzumab (Table 1). [23][24][25][30][31][32][34][35][36][37][39][40][41]44,45 Use of trastuzumab was somewhat less in patients with small ( 1 cm) and/or node-negative HER2 þ tumors, 28,30,40,41,44 in whom the benefits of adjuvant trastuzumab therapy are somewhat controversial. 7,9,10 Several studies conducted between 2006 and 2013 also suggest that older patients with HER2 þ EBC and patients with HER2 þ /hormone receptor (HR)-positive disease were less likely to receive trastuzumabbased therapy (Table 1).…”
Section: Patterns Of Use In Ebcmentioning
confidence: 99%
See 2 more Smart Citations
“…In our cohort, 3% of patients did not start with trastuzumab. Whitfield et al [15] reported for Australia and New Zealand that during 2006 and 2008, the percentage of breast cancers tested rose from 77% to 91%. In our cohort, only 4% of HER2 results were missing.…”
Section: Discussionmentioning
confidence: 99%